Reframing Human Rights in Muslim Societies: A Maqāṣid-Based Critique of Liberal Universalism through Islamic Sociological Jurisprudence - Meida Dwi Saputri; Mar’atul Firdaus; Hawa Purnama Wati; Sofia Nofita Sari; Safrida Zahra Anjani; Valeryan Resistanaya Salsabina Akin; Amanda Puji Lestari; Ahmad Muhamad Mustain Nasoha (Santri: Journal of Pesantren and Fiqh Sosial, 2026)
This article critically reassesses and reformulates liberal universalism in human rights through a maqāṣid al-sharīʿah approach integrated with Islamic sociological jurisprudence in contemporary Muslim societies. The research addresses the epistemological tension between liberal human rights norms, which are rooted in post-Enlightenment secular individualism, and the Islamic legal tradition, which prioritizes the balance between individual rights, communal obligations, and public welfare as central objectives of sharia. Utilizing a qualitative library-based methodology with normative and conceptual analysis, the study examines literature on liberal human rights theory, maqāṣid al-sharīʿah, Islamic jurisprudence, and sociological jurisprudence. The analysis is organized around three themes: Liberal Universalism and the Epistemology of Islamic Law; Maqāṣid al-Sharīʿah and Sociological Jurisprudence; and a Maqāṣid-Based Critique of Liberal Human Rights Norms. The findings indicate that maqāṣid al-sharīʿah provides a holistic and adaptive epistemological framework that addresses contemporary human rights issues while remaining grounded in Islamic legal principles. This framework facilitates the reconstruction of human rights discourse to accommodate Islamic values, social justice, collective welfare, and legal pluralism within Muslim societies. Additionally, the integration of sociological jurisprudence enhances the capacity of Islamic law to respond to evolving social realities without undermining the normative autonomy of sharia. The study concludes that a maqāṣid-based approach offers an alternative to both the dominance of liberal universalism and purely relativistic perspectives, thereby contributing to the renewal of Islamic jurisprudence and the development of a context-sensitive, normatively authentic, and socially relevant human rights framework.